A non-stoichiometric single-phase cordierite microwave dielectric ceramic, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611102928.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-16
AI Technical Summary
这一掺杂策略虽规避了稀土元素的高成本问题,且在一定程度上改善了烧结行为,但Zn²+取代所带来的性能调控往往顾此失彼——例如,介电常数、品质因数与谐振频率温度系数三者之间难以同步优化,往往需要牺牲某一参数来换取另一参数的提升,且最佳掺杂量与工艺窗口仍缺乏系统性的定量指导
(Ⅰ)本发明通过将MgO、Al2O3、ZnO和SiO2按照Mg2+x-yZnyAl4Si5O18+x的计量比配料,利用非化学计量比设计Mg2+离子固溶进入晶体结构,促进四面体层中Si/Al的有序排列,降低内层六元环的合成难度,从而拓宽烧结温度区间、提高致密性。该策略有效克服了现有技术中堇青石陶瓷烧结窗口狭窄、致密化困难的缺陷,提高了样品的致密性,大幅拓宽了堇青石陶瓷的烧结温度范围,并且降低了陶瓷样品的烧结温度,使制备出的堇青石陶瓷具备低的介电常数和低的介电损耗,以低廉的原料成本和简便的固相反应工艺即可实现堇青石基微波介质陶瓷致密度与介电性能的初步优化。
Smart Images

Figure CN122916643A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wireless communication and electronic ceramic materials technology, and specifically relates to a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. Background Technology
[0002] Electromagnetic wave communication technology is currently the most convenient and fastest way to transmit information, driving the development of human technology. With the generational leaps in mobile communication technology, microwave frequency bands are constantly expanding to higher frequencies to carry massive amounts of data and ultra-high speeds. However, frequency increases are a double-edged sword: while bringing greater bandwidth, they also face inherent bottlenecks such as increased path loss, weak diffraction ability, and susceptibility to blockage, directly affecting signal coverage and transmission stability. To overcome physical limitations, communication systems have placed higher demands on the material performance of core radio frequency devices. The development of new microwave dielectric materials has become a key foundation for promoting the development of high-frequency communication. It can not only improve the efficiency and bandwidth of components such as filters and antennas, but also is a necessary support for achieving stable operation in the high-frequency band, affecting the quality and evolution path of future information transmission. Cordierite microwave dielectric materials have excellent dielectric properties, with ultra-low dielectric constant and low loss characteristics that perfectly meet the development needs of future communication technologies. However, due to its complex crystal structure, a second phase is prone to appear during the synthesis and sintering process, which will seriously affect the densification of sintering and subsequent dielectric properties.
[0003] Currently, researchers are using ion doping methods to modify cordierite ceramics to expand the sintering range, such as replacing Mg with rare earth elements. 2+ While this improved the sample density, the high cost of rare earth elements (such as La and Nd) significantly increased the cost, hindering large-scale industrial production. Furthermore, Mg... 1.8 R 0.2 Al4Si5O 18 The study of the (R=Zn) system also confirmed that Zn 2+ For Mg 2+ The substitution of sites was investigated, and its impact on microwave dielectric properties was explored. While this doping strategy avoids the high cost of rare earth elements and improves sintering behavior to some extent, Zn²⁺… + Performance tuning resulting from substitution often involves trade-offs—for example, it's difficult to simultaneously optimize dielectric constant, quality factor, and temperature coefficient of resonant frequency, often requiring the sacrifice of one parameter to improve another. Furthermore, there's a lack of systematic quantitative guidance regarding optimal doping levels and process windows. Therefore, while Zn doping offers a feasible direction for low-cost modification, there's still a significant gap to bridge before achieving comprehensive and synergistic control of multiple performance parameters. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application, thereby solving the technical problem in the prior art of how to fully utilize the low dielectric properties of cordierite while maintaining low cost, and simultaneously ensuring a high quality factor and a suitable temperature coefficient of resonant frequency.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A non-stoichiometric polymetallic oxide, with the chemical formula Mg 2+x-y Zn y Al4Si5O 18+x Where x takes the value of 0.05, and y takes the value of 0 to 0.1. Preferably, the chemical formula of the non-stoichiometric polymetallic oxide is Mg. 2.05 Al4Si5O 18.05 Mg2Zn 0.05 Al4Si5O 18.05 Mg 1.95 Zn 0.1 Al4Si5O 18.05 Any one of them.
[0006] This invention also protects a method for preparing a non-stoichiometric single-phase cordierite microwave dielectric ceramic, the method comprising: using the aforementioned non-stoichiometric polymetallic oxide as a raw material, and synthesizing the single-phase cordierite microwave dielectric ceramic via a solid-state reaction method. The method includes the following steps: Step 1: Preparation of non-stoichiometric polymetallic oxides: Step 1.1, Ingredient Preparation: Mix MgO powder, Al2O3 powder, ZnO powder, and SiO2 powder according to the chemical formula Mg 2+x- y Zn y Al4Si5O 18+x Prepare the mixture according to the specified proportions; or mix MgO powder, Al2O3 powder, and SiO2 powder according to the chemical formula Mg 2+x- y Zn y Al4Si5O 18+x Prepare the proportions.
[0007] Step 1.2, Mixing: The raw materials prepared in Step 1.1 are ball-milled to obtain a slurry.
[0008] Step 1.3, Drying: Dry the slurry obtained in step 1.2 to constant weight to obtain a dried mixture.
[0009] Step 1.4, Pre-calcination: The mixture obtained in step 1.3 is sieved and dispersed and then pre-calcined to synthesize a non-stoichiometric polymetallic oxide pre-calcined powder.
[0010] Step 2, Preparation of cordierite-based microwave dielectric ceramics: Step 2.1, ball milling: The non-stoichiometric polymetallic oxide powder synthesized in step 1.4 is ball milled to form a non-stoichiometric polymetallic oxide slurry.
[0011] Step 2.2, Drying: Take out the non-stoichiometric polymetallic oxide slurry obtained in step 2.1 and dry it to constant weight to obtain non-stoichiometric polymetallic oxide powder.
[0012] Step 2.3, Granulation: The non-stoichiometric polymetallic oxide powder obtained in step 2.2 is sieved, then a binder is added, and the mixture is ground to make the binder and the non-stoichiometric polymetallic oxide powder evenly mixed. The mixture is sieved again to obtain a mixed powder for molding.
[0013] Step 2.4, pressing and molding: Pour the molding mixture obtained in step 2.3 into the mold and press it into a ceramic green body.
[0014] Step 2.5, Debinding and Sintering: Place the ceramic green body obtained in Step 2.4 into the furnace, first debind it, and then sinter it; after sintering, cool it down and let it cool with the furnace to obtain single-phase cordierite microwave dielectric ceramic.
[0015] Step 3, post-processing: The ceramic obtained in step 2.5 is subjected to grinding, surface polishing and ultrasonic cleaning.
[0016] This invention also protects a non-stoichiometric single-phase cordierite microwave dielectric ceramic prepared by the method described above.
[0017] This invention also protects the use of single-phase cordierite microwave dielectric ceramics with non-stoichiometric ratios as described above for the preparation of microwave communication components.
[0018] The present invention also has the following technical features: Specifically, in step 1.2, the ball milling conditions are as follows: zirconium dioxide is used as the grinding ball, anhydrous ethanol is used as the ball milling aid, and the ball milling time is 14–18 hours; the volume ratio of the raw material, grinding ball, and ball milling aid is 1:1:(1–1.5). Preferably, the ball milling time is 16 hours; and the volume ratio of the raw material, grinding ball, and ball milling aid is 1:1:1.25.
[0019] Specifically, in step 1.3, the drying temperature is 80–110 °C.
[0020] Specifically, in step 1.4, a 120-mesh standard sieve is used for sieving.
[0021] Specifically, in step 1.4, the pre-firing temperature is 1200–1400 °C, and the time is 3–5 h. Preferably, the pre-firing temperature is 1300 °C, and the time is 4 h.
[0022] Specifically, in step 2.1, the ball milling conditions are as follows: zirconium dioxide is used as the grinding ball, anhydrous ethanol is used as the ball milling aid, and the ball milling time is 10–14 h; the volume ratio of the non-stoichiometric polymetallic oxide powder, grinding ball, and ball milling aid is 1:1:(1–1.5). Preferably, the volume ratio of the non-stoichiometric polymetallic oxide powder, grinding ball, and ball milling aid is 1:1:1.25.
[0023] Specifically, in step 2.2, the drying temperature is 80–110 °C.
[0024] Specifically, in step 2.3, the first sieve is a 120-mesh standard sieve, and the second sieve is a 40-mesh standard sieve.
[0025] Specifically, in step 2.3, the binder is polyvinyl alcohol; the weight ratio of the non-stoichiometric polymetallic oxide powder to the binder is (8-12):1. Preferably, the binder is polyvinyl alcohol; the weight ratio of the non-stoichiometric polymetallic oxide powder to the binder is 10:1.
[0026] Specifically, in step 2.4, the pressing conditions are: pressing at a pressure of 80–120 MPa for 2–4 minutes. Preferably, the pressing conditions are: pressing at a pressure of 100 MPa for 3 minutes.
[0027] Specifically, in step 2.5, the conditions for adhesive removal are: heating to 550-650 °C at a rate of 2-4 °C / min and holding at that temperature for 1-3 hours. Preferably, the conditions for adhesive removal are: heating to 600 °C at a rate of 3 °C / min and holding at that temperature for 2 hours.
[0028] Specifically, in step 2.5, the sintering conditions are: heating to 1350–1425°C at a rate of 2–4°C / min and holding at that temperature for 3–5 hours. Preferably, the sintering conditions are: heating to 1350–1425°C at a rate of 3°C / min and holding at that temperature for 4 hours.
[0029] Specifically, in step 2.5, the cooling conditions are: cooling to 180-220℃ at a cooling rate of 1-3℃ / min. Preferably, the cooling conditions are: cooling to 200℃ at a cooling rate of 2℃ / min.
[0030] Compared with the prior art, the present invention has the following technical effects: (I) This invention uses MgO, Al2O3, ZnO and SiO2 in accordance with Mg 2+x-y Zn y Al4Si5O 18+x Metering ratio of ingredients, using non-stoichiometric design of Mg 2+ Ion solid solution incorporation into the crystal structure promotes the ordered arrangement of Si / Al in the tetrahedral layer, reducing the difficulty of synthesizing the inner six-membered ring, thereby broadening the sintering temperature range and improving densification. This strategy effectively overcomes the shortcomings of existing technologies, such as narrow sintering windows and difficulty in densification of cordierite ceramics. It improves the density of the samples, significantly broadens the sintering temperature range of cordierite ceramics, and lowers the sintering temperature of the ceramic samples. This results in cordierite ceramics with low dielectric constant and low dielectric loss. The initial optimization of the density and dielectric properties of cordierite-based microwave dielectric ceramics can be achieved with low raw material costs and a simple solid-state reaction process.
[0031] (II) Based on the above-mentioned non-stoichiometric design, this invention further utilizes Zn 2+ ion selectively substitutes Mg in the outer six-membered ring 2+ Sites, using Zn 2+ With Mg 2+ The similarity in ionic radii but different polarization capabilities artificially introduces localized lattice distortion into the outer six-membered ring. This distortion, through inter-ring coupling, forces an increase in the symmetry of the inner six-membered ring, effectively suppressing intrinsic dielectric loss and significantly improving the quality factor. The synergistic effect of this dual strategy significantly improves the ceramic's density, achieving a significant increase in the Q×f value while maintaining the ultra-low dielectric constant and suitable temperature coefficient of cordierite. This results in a cordierite-based microwave dielectric ceramic possessing an ultra-low dielectric constant (εr = 4.73), a high quality factor (Q×f = 118412 GHz), and a suitable temperature coefficient of resonant frequency (τf = 118412 GHz). (21.6 ppm / ℃). This dual-layer control strategy complements each other, ultimately enabling cordierite ceramics to stably achieve ultra-low dielectric constant and extremely low dielectric loss within a wide sintering temperature range.
[0032] (III) This invention reveals for the first time the microscopic mechanism of performance improvement of cordierite ceramics from the perspective of synergistic regulation of double-layer six-membered ring structure, providing a new idea for the design of subsequent high-performance microwave dielectric materials, and providing low-cost, high-performance alternative materials for microwave communication components such as resonators and filters, with broad application prospects. Attached Figure Description
[0033] Figure 1 Mg prepared according to Comparative Example 7, Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 of the present invention 2+x-y Zn y Al4Si5O18+x XRD pattern of ceramics.
[0034] Figure 2 Mg prepared according to Comparative Example 7, Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 of the present invention 2.05-y Zn y Al4Si5O 18.05 SEM image of ceramics, i.e., x = 0.05.
[0035] Figure 3 (ac) are crystal structure model diagrams drawn based on XRD-refined atomic positions for Comparative Example 7, Example 1, and Example 2 of this invention, respectively. Figure 3 (d) is Mg prepared according to Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of the present invention. 2.05-y Zn y Al4Si5O 18.05 The curves showing the variation of ceramic quality factor, inner six-membered ring distortion, and outer six-membered ring distortion with y.
[0036] The specific content of the present invention will be further explained in detail below with reference to the embodiments. Detailed Implementation
[0037] It should be noted that all raw materials used in this invention, unless otherwise specified, are those known in the art. For example, polyvinyl alcohol has a degree of polymerization of 1750±50 and a number-average molecular weight of approximately 77,000.
[0038] The technical concept of this invention is as follows: Existing Mg 1.8 R 0.2 Al4Si5O 18 Studies of the (R=Zn) system have confirmed that Zn 2+ For Mg 2+ Site substitution; however, the inventors of this application discovered through systematic research that when Zn 2+ When the substitution amount x ≥ 0.15, a weak ZnAl2O4 second-phase diffraction peak appears in the XRD pattern, indicating that Zn... 2+ Substituting Mg² in the cordierite lattice + The actual solid solution limit is below 0.20, approximately between 0.10 and 0.15. Previous literature has classified it as a single phase, possibly due to neglecting the weak peak positions. Based on these findings, this invention proposes a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. This method uses cordierite ceramic as the matrix and employs a non-stoichiometric composition design, incorporating MgO, ZnO, Al2O3, and SiO2 according to the chemical formula Mg... 2+x-y Zn y Al4Si5O18+x The ingredients were mixed in a specific ratio, where x = 0–0.10, y = 0–0.2, and x and y were not simultaneously 0. Mg was synthesized via a solid-state reaction method. 2+x-y Zn y Al4Si5O 18+x Ion-substituted nonstoichiometric cordierite-based microwave dielectric ceramics.
[0039] Following the above technical approach, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent modifications made based on the technical solutions of this application fall within the protection scope of the present invention.
[0040] Example 1 This embodiment presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method includes the following steps: Step 1: Preparation of non-stoichiometric polymetallic oxides: Step 1.1, Ingredient Preparation: Combine the raw materials MgO (99.99% purity), Al2O3 (99.99% purity), ZnO (99.99% purity), and SiO2 (99.99% purity) according to the chemical formula Mg 2.05 Al4Si5O 18.05 (i.e., Mg) 2+x-y Zn y Al4Si5O 18+x The proportions were determined by mixing ingredients with x = 0.05 and y = 0.
[0041] Step 1.2, Mixing: Place the weighed raw materials into a polytetrafluoroethylene ball mill jar, use zirconium dioxide as the grinding balls and anhydrous ethanol as the ball milling aid, and perform wet ball milling in a planetary ball mill for 16 hours. The volume ratio of powder:zirconia balls:anhydrous ethanol is 1:1:1.25 to obtain a slurry.
[0042] Step 1.3, Drying: Pour out the ball-milled slurry and place it in an oven at 80-110 ℃ to dry to constant weight, to obtain a dry mixture.
[0043] Step 1.4, Pre-calcination: The constant-weight mixture is first passed through a 120-mesh standard sieve to disperse it. Then, it is placed in a high-temperature furnace and pre-calcined in air atmosphere at a temperature of 1300 ℃ for 4 hours to synthesize Mg2Al4Si5O. 18 powder.
[0044] Step 2, Preparation of cordierite-based microwave dielectric ceramics: Step 2.1, Ball milling: The pre-sintered Mg2Al4Si5O... 18The compound powder was added to anhydrous ethanol and ball-milled for 12 hours to form Mg2Al4Si5O. 18 Slurry.
[0045] Step 2.2, Drying: Drying Mg2Al4Si5O 18 The compound slurry was removed and dried in an oven at 80 °C to constant weight to obtain Mg2Al4Si5O. 18 Compound powder.
[0046] Step 2.3, Granulation: The dried Mg2Al4Si5O 18 The compound powder is first passed through a 120-mesh standard sieve, and then polyvinyl alcohol (PVA) binder is added. The weight ratio of the compound powder to the polyvinyl alcohol is 10:1. The mixture is ground in an agate mortar and pestle to make it evenly mixed with the raw materials, and then passed through a 40-mesh standard sieve to obtain a mixed powder for molding.
[0047] Step 2.4, pressing and molding: Pour the molding powder mixture into the mold, and then press it in a tablet press at a pressure of 100 MPa for 3 minutes to form a ceramic green body with a diameter of 12 mm and a height of 7 mm.
[0048] Step 2.5, Debinding and Sintering: Place the pressed green body into a high-temperature furnace, set the furnace heating rate to 3℃ / min, heat to 600℃ and hold for 2 hours to debind. Then raise the temperature to the corresponding temperature at the same heating rate. The sintering temperature range is 1350~1425℃ (see Table 1 for specific temperatures), hold for 4 hours, and then lower the temperature to 200℃ at a cooling rate of 2℃ / min. Stop the program and allow the furnace to cool down naturally.
[0049] Step 3, post-processing: The sintered sample is sanded to 3000 grit and then polished, followed by ultrasonic cleaning.
[0050] Example 2 (Best Example) This embodiment presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg2Zn. 0.05 Al4Si5O 18.05 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0051] Example 3 This embodiment presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method is essentially the same as in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg... 1.95 Zn 0.1 Al4Si5O18.05 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0052] Comparative Example 1 This comparative example provides a method for preparing a non-stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg 1.9 Zn 0.15 Al4Si5O 18.05 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0053] Comparative Example 2 This comparative example provides a method for preparing a non-stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg 1.85 Zn 0.2 Al4Si5O 18.05 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0054] Comparative Example 3 This comparative example provides a method for preparing a non-stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg 2.05 Zn 0.05 Al4Si5O 18.1 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0055] Comparative Example 4 This comparative example provides a method for preparing a non-stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg2Zn. 0.1 Al4Si5O 18.1 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0056] Comparative Example 5 This comparative example provides a method for preparing a non-stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg 1.95 Zn 0.15 Al4Si5O 18.1 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0057] Comparative Example 6 This comparative example provides a method for preparing a non-stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg 1.9 Zn 0.2 Al4Si5O 18.1 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0058] Comparative Example 7 This comparative example provides a method for preparing a stoichiometric dual-phase cordierite microwave dielectric ceramic, which is basically the same as that in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg2Al4Si5O 18 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0059] Comparative Example 8 This comparative example presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method is essentially the same as in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg... 1.95 Zn 0.05 Al4Si5O 18 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0060] Comparative Example 9 This comparative example presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method is essentially the same as in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg... 1.9 Zn 0.1 Al4Si5O 18 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0061] Comparative Example 10 This comparative example presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method is essentially the same as in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg... 1.85 Zn 0.15 Al4Si5O 18 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0062] Comparative Example 11 This comparative example presents a non-stoichiometric single-phase cordierite microwave dielectric ceramic, its preparation method, and its application. The method is essentially the same as in Example 1, except that in step 1.1, the raw materials are prepared according to the chemical formula Mg... 1.8 Zn 0.2 Al4Si5O18 Properly proportion the materials. For step 2.5, the specific sintering temperatures are shown in Table 1.
[0063] Table 1, Mg 2+x-y Zn y Al4Si5O 18+x Composition and dielectric properties of microwave dielectric ceramics
[0064] Figure 1 The XRD patterns of Comparative Example 7, Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 are obtained by comparing them with Zn through non-stoichiometry. 2+ Dual regulation through ion substitution addresses the challenge of ceramic formation at lower sintering temperatures for cordierite ceramics with stoichiometric ratios. Sintering at 1400 °C, due to the high temperature, results in the disordered arrangement of some Si / Al ions, forming diffraction peaks of the disordered intraite phase at high temperatures, hindering densification. By employing non-stoichiometric compositional design, the formation of the disordered intraite phase at high temperatures is suppressed at the source, ensuring the purity of the ordered bilayer six-membered ring structure of cordierite and paving the way for subsequent outer Zn²⁺ layers. + This laid the foundation for replacing regulation. Further, through Zn... 2+ Ion-substituted Mg 2+ At the site, single-phase cordierite ceramics were successfully synthesized when x = 0.05 and y = 0, 0.05, and 0.10 (i.e., Examples 1, 2, and 3). When y = 0.15 and 0.20, the concentration exceeded that of Zn. 2+ The solid solubility limit of the ions, with the appearance of diffraction peaks of the ZnAl2O4 second phase, proves that the solid solubility limit of cordierite is between 0.10 and 0.15.
[0065] Based on non-stoichiometry, this invention further introduces Zn. 2+ Ion substitution design. The key lies in: Zn 2+ With Mg 2+ Although the ionic radii are almost identical (0.73 Å vs 0.72 Å), Zn 2+ The polarization ability is significantly stronger than that of Mg. 2+ This makes Zn 2+ Mg preferentially occupies the outer six-membered ring 2+ At the site, significant local lattice distortion will occur on the outer six-membered ring (e.g. Figure 3 The data shows how the distortion parameters of the middle and outer layers change with increasing y. Figure 3(ac) shows a refined crystal structure model of cordierite along the c-axis, where the inner six-membered ring consists of four [SiO4] and two [AlO4] tetrahedra, and the outer six-membered ring consists of two [SiO4] and four [AlO4] tetrahedra connected to six [Mg / ZnO6] octahedra. The two layers of six-membered rings are interconnected by a common apex oxygen atom. According to the crystallographic coupling effect, the distortion of the outer six-membered ring is transferred through inter-ring chemical bonds, forcing the inner six-membered ring to adopt a more symmetrical configuration to reduce the total energy of the system, such as... Figure 3 (d) confirms that the inner layer distortion parameter decreases with increasing y. The improvement in the symmetry of the inner layer six-membered ring directly reduces the anharmonicity of the phonon mode, thereby effectively suppressing the intrinsic dielectric loss, which is manifested as a significant improvement in the quality factor Q×f (as shown in Table 1 above).
[0066] Combined Figure 2 (SEM images of Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2) When y = 0, the sintered ceramic grains are relatively small. When y = 0.05 and 0.1, the Zn... 2+ The introduction of ions helps promote grain growth, thereby reducing dielectric loss caused by grain boundary scattering. Subsequently, as the y-value continues to increase, a second ZnAl2O4 phase appears inside the ceramic sample, increasing extrinsic losses due to the phase interface and thus reducing dielectric properties. This demonstrates that non-stoichiometric composition design reduces extrinsic losses caused by porosity and grain boundary scattering; while Zn... 2+ Substitution reduces intrinsic loss by controlling the lattice distortion distribution of the bilayer six-membered ring. Figure 3 The two mechanisms operate at the intrinsic and extrinsic levels, respectively, and together achieve comprehensive optimization of dielectric properties.
Claims
1. A non-stoichiometric polymetallic oxide, characterized in that, The chemical formula for this polymetallic oxide is Mg. 2+x-y Zn y Al4Si5O 18+x , where x takes the value of 0.05 and y takes the value of 0 to 0.
1.
2. A method for preparing a non-stoichiometric polymetallic oxide as described in claim 1, characterized in that, The method includes the following steps: Step 1.1, Ingredient Preparation: Mix MgO powder, Al2O3 powder, ZnO powder, and SiO2 powder according to the chemical formula Mg 2+x- y Zn y Al4Si5O 18+x Prepare the mixture according to the specified proportions; or mix MgO powder, Al2O3 powder, and SiO2 powder according to the chemical formula Mg 2+x- y Zn y Al4Si5O 18+x Mix the ingredients according to the specified proportions; Step 1.2, Mixing: The raw materials prepared in Step 1.1 are ball-milled to obtain a slurry; Step 1.3, Drying: Dry the slurry obtained in step 1.2 to constant weight to obtain a dried mixture; Step 1.4, Pre-calcination: The mixture obtained in step 1.3 is sieved and dispersed and then pre-calcined to synthesize a non-stoichiometric polymetallic oxide pre-calcined powder.
3. The method for preparing non-stoichiometric polymetallic oxides as described in claim 2, characterized in that, In step 1.2, the ball milling conditions are as follows: zirconium dioxide is used as the grinding ball, anhydrous ethanol is used as the ball milling aid, and the ball milling time is 14-18 hours; the volume ratio of the raw material, grinding ball and ball milling aid is 1:1:(1-1.5). In step 1.4, the pre-firing temperature is 1200-1400 ℃ and the time is 3-5 h.
4. A method for preparing a non-stoichiometric single-phase cordierite microwave dielectric ceramic, characterized in that, The method includes: using the non-stoichiometric polymetallic oxides of claim 1 as raw materials, and synthesizing single-phase cordierite microwave dielectric ceramics by solid-state reaction.
5. The method for preparing non-stoichiometric single-phase cordierite microwave dielectric ceramics as described in claim 4, characterized in that, The method includes the following steps: Step 1: Prepare non-stoichiometric polymetallic oxides; Step 2, Preparation of cordierite-based microwave dielectric ceramics: Step 2.1, ball milling: The non-stoichiometric polymetallic oxide powder synthesized in step 1.4 is ball milled to form a non-stoichiometric polymetallic oxide slurry; Step 2.2, Drying: Take out the non-stoichiometric polymetallic oxide slurry obtained in Step 2.1 and dry it to constant weight to obtain non-stoichiometric polymetallic oxide powder; Step 2.3, Granulation: The non-stoichiometric polymetallic oxide powder obtained in step 2.2 is sieved, then a binder is added, and the mixture is ground to make the binder and the non-stoichiometric polymetallic oxide powder evenly mixed. The mixture is sieved again to obtain a mixed powder for molding. Step 2.4, Pressing and Molding: Pour the molding mixture obtained in Step 2.3 into a mold and press it into a ceramic green body; Step 2.5, Debinding and Sintering: Place the ceramic green body obtained in Step 2.4 into the furnace, first debind it, and then sinter it; after sintering, cool it down and let it cool with the furnace to obtain single-phase cordierite microwave dielectric ceramic. Step 3, post-processing: The ceramic obtained in step 2.5 is subjected to grinding, surface polishing and ultrasonic cleaning.
6. The method for preparing non-stoichiometric single-phase cordierite microwave dielectric ceramics as described in claim 5, characterized in that, In step 2.1, the ball milling conditions are as follows: zirconium dioxide is used as the grinding ball, anhydrous ethanol is used as the ball milling aid, and the ball milling time is 10-14 hours; the volume ratio of the non-stoichiometric polymetallic oxide powder, grinding ball and ball milling aid is 1:1:(1-1.5). In step 2.3, the binder is polyvinyl alcohol; the weight ratio of the non-stoichiometric polymetallic oxide powder to the binder is (8-12):
1.
7. The method for preparing non-stoichiometric single-phase cordierite microwave dielectric ceramics as described in claim 5, characterized in that, In step 2.4, the pressing conditions are: pressing for 2 to 4 minutes at a pressure of 80 to 120 MPa.
8. The method for preparing non-stoichiometric single-phase cordierite microwave dielectric ceramics as described in claim 5, characterized in that, In step 2.5, the conditions for degreasing are: heating at a rate of 2-4℃ / min to a temperature of 550-650℃ and holding at that temperature for 1-3 hours; In step 2.5, the sintering conditions are: heating at a rate of 2-4℃ / min to a temperature of 1350-1425℃ and holding at that temperature for 3-5 hours; In step 2.5, the cooling condition is: cooling down to 180-220℃ at a cooling rate of 1-3℃ / min.
9. A non-stoichiometric single-phase cordierite microwave dielectric ceramic, characterized in that, It is prepared by the preparation method described in any one of claims 4 to 8.
10. The application of the non-stoichiometric single-phase cordierite microwave dielectric ceramic as described in claim 9 in the preparation of microwave communication components.